Μεταβυζαντινοί σύνθετοι και ημισύνθετοι τετρακιόνιοι σταυροειδείς εγγεγραμμένοι ναοί της Πελοποννήσου - ΜΕΣΣΗΣ Βασίλειος Δ. (Byzantina Symmeikta, 2015)
Complex and semi-complex cross in-square four columned post Byzantine churches in Peloponnese, Greece Post Byzantine churches in Peloponnese that belong to the two variations of the four columned cross in-square type, the complex and the semi-complex, differ from each other but at the same time share much in common. They can also be classified in groups. Ιn general terms, the application of the type in post Byzantine Peloponnese expresses the middle Byzantine tradition, whereas the churches built by the beginning of 18th century show a removal from that tradition. Moreover we can realise the close typological relationship between athonite type churches (complex cross in-square four columned type with side choirs churches), and complex cross in-square four columned type without side choirs churches in Peloponnese. To conclude, we could refer to the strong connection between post Byzantine church construction in Peloponnese and its Byzantine origins. This connection is so powerful and vivid that one can easily seek it both in the choice of church types that flourished in the Middle Byzantine period and in the persistent repetition of many characteristics of those types.